MicroRNA-200a Promotes Phagocytosis of Macrophages and Suppresses Cell Proliferation, Migration, and Invasion in Nasopharyngeal Carcinoma by Targeting CD47 - Zhao, Yunteng (Biomed Res Int, 2020)
Nasopharyngeal carcinoma (NPC) causes severe oncogenic lesions in the nasopharynx. CD47, a transmembrane integrin-associated protein, plays a key role in the ability of tumor cells to escape phagocytosis, working as an immune checkpoint in the immune response. Besides this role, CD47 has been reported to regulate cell proliferation and migration. The present study addresses the relationship between CD47 and microRNA-200a and examines their regulatory mechanisms in NPC. Bioinformatics analyses and dual-luciferase reporter assays were used to confirm the putative relationship between miR-200a and CD47, and their interaction was further detected using western blotting and RT-PCR. Further, results showed that miR-200a affect NPC cell proliferation, migration, and invasion by regulating CD47. A cell phagocytosis assay showed that miR-200a and a CD47 monoclonal antibody increased the sensitivity of NPC cells to macrophage phagocytosis by inhibiting the functions of CD47. Additionally, miR-200a expression was suppressed and CD47 expression increased in both clinical NPC tissues and cell lines. Taken together, these results show the miR-200a/CD47 combination as a potential therapeutic for treatment of NPC.